Controlled Brushless De-Excitation Structure for Synchronous Generators - Chouaba, S. E.; Barakat, A. (Engineering, Technology & Applied Science Research, 2019)
The main weakness of the brushless excitation system in a synchronous generator (SG) is the slow de-excitation response obtained during a load rejection. That is why voltage overshoots may be observed on the generator terminals. This behavior is mainly due to the exciter machine response time and the rotating diode bridge which is not able to quickly de-excite the generator by negative excitation voltages. This paper presents a new brushless de-excitation structure able to perform a quick de-excitation of the generator by providing controlled negative excitation voltage to the generator main field winding. The proposed structure is based on a new brushless de-excitation machine, called a control machine, and mounted on the same shaft of the generator and the brushless exciter. The brushless control machine is a low power one and used to transfer the orders from the voltage regulator to the discharge system located on the rotor side of the main generator. The dynamic performance of the proposed de-excitation system is evaluated in terms of system stability, voltage regulation response times and voltage overshoots during different load rejection tests. The proposed system is compared to the conventional brushless excitation system without the proposed de-excitation structure. In addition, a comparison is done with the static excitation system. The simulation tests are realized on an experimentally validated model of 11kVA synchronous generator developed in Matlab/Simulink.